ANALISIS PENERAPAN ASESMEN FORMATIF DALAM PEMBELAJARAN IPA DAN FISIKA : LITERATURE REVIEW - Dwi Putri Ramadhani (LENSA (Lentera Sains): Jurnal Pendidikan IPA, 2021)
In the 21st century education demands the creation of quality students. One of the methods used is to apply formative assessment in learning. The purpose of this study was to determine the application of formative assessment based on student learning outcomes, education level, learning materials, and integration used. In this study using a literature study (library research) with a literature review approach. The articles used are in the 2015-2020 range. The results of this study are: 1) the use of formative tests can improve various student learning outcomes where the most measured is the understanding/mastery of concepts, 2) the application of formative assessments is more widely used at the junior high school level compared to the high school level, 3) the application of formative assessments in science learning and physics consists of various materials which indicate formative assessment is often used in learning, and 4) there are various kinds of integration used in formative assessment where the most widely used is integrating formative assessment with the web.